The new consensus view of monetary policy: a new Wicksellian connection? - Giuseppe Fontana (Levy Economics Institute of Bard College, 2006)
One of the greatest achievements of the modern New Consensus view in macroeconomics is the assertion of a nonquantity theoretic approach to monetary policy. Leading theorists and practitioners of this view have indeed rejected the quantity theory of money, and defended a return to the old Wicksellian idea of eliminating high levels of inflation by adjusting nominal interest rates to changes in the price level. This paper evaluates these recent developments in the theory and practice of monetary policy in terms of two basic questions: 1) What is the monetary policy instrument controlled by the central bank? and 2) Which macroeconomic variables are affected in the short and long run by monetary policy?
Keywords: E5; E52; 330; Wicksell; monetary policy; New Consensus; endogenous Money